Tracking progress toward elimination of iodine deficiency disorders in Jharkhand, India - Patro Binod; Saboth Prasant; Zodpey Sanjay; Shukla Amit; Karmarkar Madhu; Pandav Chandrakant (Wolters Kluwer Medknow Publications, 2008)
Research question: What is the current status of Iodine Deficiency Disorders (IDD) in the state of Jharkhand? Objectives: (1) To determine the status of iodine deficiency in the state. (2) To determine the availability and cost of adequately iodized salt at the retail shops. (3) To study the perceptions of the community regarding iodine deficiency, salt and iodized salt. Design: A cross-sectional community-based survey. Study setting: Thirty clusters selected through the probability proportion to size (PPS) sampling in the state of Jharkhand. Study participants: Children aged 6-12 years, households, retail shopkeepers and opinion leaders. Study tool: Quantitative and qualitative methodology using a pretested questionnaire and focus group discussion used to carry out the community-based survey. Results: Total goiter rate (TGR) was 0.9%. Median urinary iodine level was 173.2 µg/L. The proportion of individuals with urinary iodine levels less than 100 and 50 µg/L were 26.4% and 10%, respectively. Slightly less than two-thirds (64.2%) of the households were found to be consuming adequately iodized salt as measured by titration (greater than 15 ppm). Iodized salt was available across the state and the cost varied between Re. 1 and Rs. 8 per kilogram. A common belief among the community was that iodized salt is equivalent to refined packet salt that is further equivalent to expensive salt. Conclusion: The results of the present survey show that the iodine nutrition in the state of Jharkhand is optimal. Considering that the consumption of adequately iodized salt should increase from 64.2% to the goal of more than 90%, sustained efforts are required in this place to consolidate the current coverage of adequately iodized salt and increase it to greater than 90%.